2019
DOI: 10.21203/rs.2.19617/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Irradiation pretreatment enhances the therapeutic efficacy of platelet-membrane- camouflaged antitumor nanoparticles

Abstract: Backgroud: Cell membrane-based nanocarriers are promising candidates for delivering antitumor agents. The employment of a simple and feasible method to improve the tumor-targeting abilities of these systems is appealing for further application. Herein, we prepared a platelet membrane (PM)-camouflaged antitumor nanoparticle. The effects of irradiation pretreatment on tumor targeting of the nanomaterial and on its antitumor action were evaluated.Results: The biomimetic nanomaterial constructed by indocyanine gre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Flow cytometry was performed as we have recently described. 38 Briefly, HK-2 was seeded into 6-well plates at a density of 2 × 10 5 cells per well and cultured overnight in DMEM containing 10% FBS. The cells were coincubated with 100 ng mL –1 S1 and D614G-S1 for 24 h in the absence and presence of NP (100, 50, and 10 μg mL –1 , based on the membrane protein) pretreatment.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry was performed as we have recently described. 38 Briefly, HK-2 was seeded into 6-well plates at a density of 2 × 10 5 cells per well and cultured overnight in DMEM containing 10% FBS. The cells were coincubated with 100 ng mL –1 S1 and D614G-S1 for 24 h in the absence and presence of NP (100, 50, and 10 μg mL –1 , based on the membrane protein) pretreatment.…”
Section: Methodsmentioning
confidence: 99%
“…Photothermal conversion then increases the temperature of the tumor tissue, thereby damaging tumor cells through protein denaturation and membrane disruption [ 74 , 75 ]. In recent years, several studies have demonstrated that the heat generated by nano-photothermal materials not only has the effect of directly killing tumor cells, it can also inhibit tumor metastasis [ 76 78 ]. In addition, nano-photothermal materials can also be used in bioimaging, and they may also be modified in such a way as to impart properties that may be beneficial to chemotherapy, radiotherapy, and immunotherapy, making them effective multifunctional diagnostic and therapeutic agents against tumors [ 79 , 80 ].…”
Section: Chiral Nanomaterials For Photothermal Tumor Therapymentioning
confidence: 99%
“…The resulting cell membrane camouflaged NPs preserve the physicochemical properties of the NP core while possessing the complex components of a natural cell membrane, which might endow the NPs with many desirable biological functions. Recently, a variety of cells except red blood cells (RBCs), including platelets, immune cells (e.g., macrophages), and cancer cells have been used to obtain membrane materials [26][27][28][29]. Compared with single cell membrane, hybrid cell membrane-coating approach can endow synthetic NPs with multifunctional and complex cell-like functions [30].…”
Section: Introductionmentioning
confidence: 99%